2020
DOI: 10.1111/ajt.15654
|View full text |Cite
|
Sign up to set email alerts
|

A gut microbiota score predicting acute graft-versus-host disease following myeloablative allogeneic hematopoietic stem cell transplantation

Abstract: Although studies have reported that intestinal microbiota are associated with acute graft‐versus‐host disease (aGVHD), they lacked a satisfactory method for predicting aGVHD. We collected stool and blood samples at day 15 posttransplant from 150 patients from two centers who underwent myeloablative conditioning allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Stool microbiota were detected by 16S ribosomal RNA gene sequencing; inflammatory factors and T lymphocytes were detected by multiplex imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…32 To improve the prognostic values for clinical outcomes, studies also tried to establish microbiota-compositional score systems. 5,33 Nevertheless, it is currently unrealistic to predict clinical outcome through precise characterization of an individual intestinal microbiota.…”
Section: B Cmentioning
confidence: 99%
“…32 To improve the prognostic values for clinical outcomes, studies also tried to establish microbiota-compositional score systems. 5,33 Nevertheless, it is currently unrealistic to predict clinical outcome through precise characterization of an individual intestinal microbiota.…”
Section: B Cmentioning
confidence: 99%
“…Higher diversity of intestinal microbiota at the time of neutrophil engraftment was associated with lower mortality [9]. The microbiota can be used as predictor of mortality in allo-HSCT [10], and the constitution of the intestinal microbiota at neutrophil engraftment and GM score can predict the development of aGvHD following myeloablative allo-HSCT [24,25]. These results supported the idea for modulation of the GM in patients with HSCT.…”
Section: Introductionmentioning
confidence: 52%
“…A study by Han L et al. found more gut microbiota diversity in the non-aGVHD group than in the aGVHD group ( 91 ), they evaluated the gut microbiota to predict GVHD and found that Lachnospiraceae and Peptostreptococcaceae were negatively associated with GVHD, while Enterobacteriaceae were positively associated with aGVHD ( 91 ). Lachnospiraceae was negatively correlated with severe aGVHD, and levels of all major SFCAs were significantly decreased in patients with severe aGVHD, with a 75.8% decrease in acetate, a 95.8% decrease in propionate, and a 94.6% decrease in butyrate, while propionate levels were retained in patients with mild aGVHD.…”
Section: The Place Of Gut Microbiota In Allo-hsct: For Better or For Worse?mentioning
confidence: 99%